Table tennis an alternative avenue towards health and fitness - Salangsang, Marie Toni A. (2008)
Humans are the central figures of an environment. Becoming effective manages of the natural world entails humans to be physically fit and mentally sound. It is essential that humans engage in physical activities that will ensure the improvement of their overall health and fitness. This study reviews table tennis as an activity high can provide its practitioners with the multiple facets of health and fitness benefits. Gathering data for other significant researches, table tennis is proven to be an excellent choice of physical activity that addresses health and fitness benefits. Interviews from both table tennis and non-table tennis enthusiasts express the social acceptability and practicality of the sport. As an alternative physical activity, table tennis offers humans two major benefits as the prime effectors of the environment. The sport further grants mental and psychological benefits that permit humans to be sound decision makers of their environment.
Keywords: Table tennis; Physical fitness; Cardiovascular fitness; Environmental health